The mechanism of adopting political decisions in the EU on the example of European Rail Infrastructure Managers - Bugajski, Wojciech (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2019)
The process of decision-making, lobbying and negotiating formal and legal documents is a complex but also very interesting issue. Referring to the findings of the studies in the field of shaping public policy, in particular the process of making political decisions on the example of European Rail Infrastructure Managers, one of the leading interest group organisations, the thesis put forward in the research process: “The decision-making process in the European Union is a difficult art of seeking compromise and understanding for stakeholders” appears to be justified.